2004
DOI: 10.1093/jnen/63.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Matrix Metalloproteinase-3 and Agrin Cleavage in Cerebral Ischemia/Reperfusion

Abstract: Matrix metalloproteinase-3 (MMP-3) degrades components of the extracellular matrix and may participate in the pathogenesis of stroke. Here we examine the expression, activation, and cellular location of MMP-3 and the cleavage of agrin, an MMP-3 substrate, following transient middle cerebral artery occlusion in the rat. MMP-3 was activated by ischemia/reperfusion, which was revealed by the appearance of a cleaved form and increased degradation of a substrate. MMP-3 was observed in ischemic neurons, oligodendroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 53 publications
0
75
1
Order By: Relevance
“…Furthermore, Solé et al (2004) observed Agrn staining in glia after cerebral ischemia. Incidentally, we did not observe the ischemia-induced 135 kDa Agrn fragment reported by Solé et al (2004) in ISC synaptosomes. This may be due to a lack of MMP3 degradation of synaptic Agrn in the 3 to 20 h time frame or loss of the nonmembrane-associated Agrn fragment during the synaptosomal isolation procedure.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Solé et al (2004) observed Agrn staining in glia after cerebral ischemia. Incidentally, we did not observe the ischemia-induced 135 kDa Agrn fragment reported by Solé et al (2004) in ISC synaptosomes. This may be due to a lack of MMP3 degradation of synaptic Agrn in the 3 to 20 h time frame or loss of the nonmembrane-associated Agrn fragment during the synaptosomal isolation procedure.…”
Section: Discussionmentioning
confidence: 92%
“…Various studies in human and rat brains show that protein and activity levels of MMPs-2, -3, and -9 are increased after stroke and MCAO compared to control tissue. 173,174 These changes in MMP protein and activity levels result in aberrant proteolysis that contributes to blood-brain barrier dysfunction and in part determines the extent of the infarct. 132,[173][174][175][176][177] In addition, studies using rat stroke models suggest that by degrading the basal lamina, MMPs predispose brain capillaries to rupture and hemorrhagic transformations after stroke.…”
Section: Strokementioning
confidence: 99%
“…173,174 These changes in MMP protein and activity levels result in aberrant proteolysis that contributes to blood-brain barrier dysfunction and in part determines the extent of the infarct. 132,[173][174][175][176][177] In addition, studies using rat stroke models suggest that by degrading the basal lamina, MMPs predispose brain capillaries to rupture and hemorrhagic transformations after stroke. [178][179][180] Other examples of detrimental MMP effects in stroke were shown in studies using rodent models of focal cerebral ischemia.…”
Section: Strokementioning
confidence: 99%
“…Collagen degradation after cerebral ischemia might be in part caused by MMP-13 [43]. Another matrix metalloproteinase, MMP-3 can also be activated after ischemia in rat brain, causing cleavage of the cerebral matrix agrin [82]. MMP-3 can contribute to BBB opening during neuroinflammation after intra-cerebral lipopolysaccharide injection in mice.…”
Section: Targets Of Mmps In the Cnsmentioning
confidence: 99%